Dinamika Psiko-sosial Remaja dalam Belajar: Analisis Masalah Psiko-sosial Siswa SMU - Endang Poerwanti (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
The Psychosocial Dynamics of Adolescent in Learning: An Analysis to the Psychosocial Problems of Senior High School (SMU) Students. This study analyse the psychosocial problems of SMU students in learning. The sample consisted of students and teachers of public and private SMUs in Malang. A questionnaire was used to collect data, which were then analyzed qualitatively. It could be concluded that the adolescents were facing serious problems relating to need for affiliation, self actualization, gender role, and continuing education. The public school students were experiencing more serious problems in competition, need for achievement, and social adjustment. The serious problems faced by private students were motivation and concentration, discipline, resposibility, self-confidence, and perception on reality.